Use of the Flip Application in Fintech Transactions from an Islamic Economic Perspective: Wahdah Islamiyah Cadre Flip User Study - Bachtiar, Muhammad Harsya; Hamzah, Nasir; Siradjuddin, Siradjuddin; Kadir, Amiruddin (Journal of Modern Islamic Studies and Civilization, 2024)
The development of financial technology (fintech) has given rise to various financial service applications, including the Flip application. Flip provides a variety of technology-based financial services, such as interbank transfers, buying credit, and E-Wallet top-ups. The Flip application is widely used by the general public, including cadres of the Wahdah Islamiyah mass organization. This research examines fintech transactions from an Islamic perspective, tracing fintech contracts in the Flip application, and the views of Wahdah Islamiyah cadres regarding the use of the Flip application in fintech transactions from an Islamic economic perspective. This research uses qualitative methods with descriptive analysis and a grounded theory approach. Observation, interviews, and documentation all played a role in the data collection process. The results of this research show that: 1) in Islamic terms, fintech is something that is permitted as long as it is free from prohibited elements such as usury, gharar, maysir, tadlis, dharar, zhulm, and haram. 2) Fintech contracts in the Flip application are wakalah, wakalah bil ujrah, and bay' (buying and selling) contracts, which are basically permitted. 3) Flip users among Wahdah Islamiyah cadres view that Flip services such as interbank transfers, credit purchases, and E-Wallet top-ups are in accordance with Islamic economic principles because they are free from usury, gharar, and dharar and contain maslahah and taysir (convenience). Implications of this research: 1) The socialization of Islamic economic principles in fintech-based financial services is needed. 2) can develop research on other fintech features of the Flip application.